(untitled) (Journal of Contemporary Philology, 2023)
The paper deals with the exploration of the primary tendencies and prerequisites for the appearance of the expressionistic epoch in the German language poetry. Opposing aspects are interwoven in expressionism, as a period that’s characterized by strong criticism of the culture and civilization in which the subjects experience an identity crisis. The destruction of the values of the human I, as well as the need for internal transformation are evident. The goal of this paper is to determine the aspects of the influence of the philosophical theory of Friedrich Nietzsche on the spiritual climate of expressionism. It investigates his conception of nihilism and the study on superhuman, as well as the Christian study for transforming and creating the new man. The implications of these concepts are apparent in the choice of verses of anthology of the expressionistic lyric Dawning of humanity by Albert Ehrenstein, Kurt Heynicke, Walter Hasenclever and Alfred Wolfenstein.